A naturalistic analysis of rTMS treatment outcomes for major depressive disorder in West Australian youth - Miljevic, Aleksandra; Hoath, Kyle; Leggett, Kerry S.; Hennessy, Lauren A.; Boax, Caitlan A.; Hryniewicki, Jaroslaw; Rodger, Jennifer (Frontiers in Psychiatry, 2025)
ObjectiveRepetitive transcranial magnetic stimulation (rTMS) is an effective, evidence-based treatment for major depressive disorder (MDD) in adults and is publicly funded in Australia. However, there is limited data as to its efficacy and safety in treating MDD in adolescent and youth populations.MethodsThis retrospective report examined routinely collected data of 46 outpatients aged 17 to 25 years old, who received rTMS treatment for MDD in a private TMS clinic. Primary outcomes measures were the Montgomery-Asberg Depression Rating Scale (MADRS) and the depression subscale of the 21-item Depression, Anxiety and Stress Scale (DASS-21). Secondary measures included the anxiety and stress sub-scales of the DASS-21, a measure of Quality of Life (QoL) Enjoyment and Satisfaction Questionnaire, and the Cognitive Failures Questionnaire (CFQ).ResultsA 4–7-week course of rTMS significantly reduce symptoms of self-reported depression (42.5% response) and clinician-assessed depression (40.7% response). Both anxiety and stress significantly reduced across the course of rTMS treatment and significant improvements to QoL and self-reported cognition were observed. Reported side effects following rTMS in youth included a mild headache and fatigue.ConclusionsThe findings of this naturalistic report suggest that an acute course of rTMS is safe and effective – resulting in similar response rates in adolescent and youth patients as reported in adults. Future large-scale, randomized, and sham-controlled trials are needed to consolidate and add to these findings.